Egalitarianism and public perception of social inequities: A case study of Beijing congestion charge. (February 2019) - Liu, Qiyang; Lucas, Karen; Marsden, Greg; Liu, Yang
Abstract: Egalitarian thought has a long tradition in Chinese history. Synthesized with the socialist ideology, it was practiced nationwide in the first decades of Communist China. Alongside the well-reported quality of life improvements that the recent economic liberalisation reforms have brought about, Chinese people are experiencing an increasingly serious polarization between the rich and the poor. Consequently, an egalitarian tendency has represented itself within contemporary policy and popular discourse. This paper aims to explore how egalitarian thought has influenced public awareness of social inequities by using the case of public attitudes towards the Beijing congestion charge, which is currently still at its planning stage. Nine focus groups, with a total of 73 participants, were undertaken with residents living in different areas of the city. Results show that the perceptions of social inequities are significantly different between low-income and high-income people. Due to egalitarian thinking, low-income people expect the privileges of the rich to be abolished, however, they do not pay much attention to a wider redistribution of wealth and other social resources. By contrast, richer people tend to deny to a wider population the privileges they themselves received, and, to some extent, they are reluctant to accept policy outcomes that may favour those who are in lower social positions. The resentment against the rich, as another by-product of egalitarianism, considerably exaggerates actual social inequalities, thereby intensifying the feelings of being unequally treated. Highlights: Equity issues of congestion charging in the Chinese context are explored via focus group discussions. Four types of inequities related to congestion charging are identified. Chinese egalitarianism influences perceived inequities and intensify the feeling of being oppressed. Chinese egalitarianism leads to an expectation of privilege deprivation.